1979
DOI: 10.1128/aac.16.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Human Pharmacology of Cefotaxime (HR 756), a New Cephalosporin

Abstract: Cefotaxime (HR 756) is a new senisynthetic parenteral cephalosporin with exceptional activity against gram-negative organisms and considerable stability against their f,-lactamases. To study its pharmacokinetic properties, 0.5-, 1-, and 2-g doses were administered to each of six volunteers intravenously over 15 mi, followed by a sustaining infusions of 0.5, 1, and 2 g/h, respectively, for 3 consecutive hours. The loading doses produced mean peak levels of 41, 93, and 160 .g/ ml, and mean steady-state serum con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
39
3

Year Published

1980
1980
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 20 publications
7
39
3
Order By: Relevance
“…The serum levels after 1 g (Table 3) are in agreement with previously published findings, including the presence of residual antimicrobial activity up to 6 h after dosing (8,14,19 levels for up to 6 h after i.v. or i.m.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The serum levels after 1 g (Table 3) are in agreement with previously published findings, including the presence of residual antimicrobial activity up to 6 h after dosing (8,14,19 levels for up to 6 h after i.v. or i.m.…”
Section: Discussionsupporting
confidence: 81%
“…The human pharmacology of cefotaxime is similar to that of most currently available cephalosporins, but its half-life of approximately 1 h is twice as long as that of cephalothin (7,14,19). The serum levels after 1 g (Table 3) are in agreement with previously published findings, including the presence of residual antimicrobial activity up to 6 h after dosing (8,14,19 levels for up to 6 h after i.v.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The major route of elimination for moxalactam is via the kidneys. We found a mean of 61% in the urine, which is similar to the 55 to 76% reported by others (24,29,32,35 (7,9,10,12,22) and 76.1 min calculated from our own data, is much more rapid than that of cefoperazone (1,6,33,34) and moxalactam (19,29,35,36 Elimination of cefotaxime is rapid, with about 90% of the dose recovered in urine by HPLC, of which two-thirds is detected as unchanged cefotaxime and one-third as the major metabolite desacetyl cefotaxime. Bax et al (2) reported a total urine recovery of 87% with 35% as desacetylated metabolite, compared with a total recovery rate of 89.6% with 29.1% as metabolite in our study.…”
Section: Methodssupporting
confidence: 77%
“…Cefotaxime (formerly HR 756) is a new cephalosporin agent much acclaimed for its broad spectrum of in vitro antimicrobial activity (2,3,5,(11)(12)(13) and its beta-lactamase resistance and beta-lactamase inhibitory activity (5,6,8). Interpretive zone standards for the disk diffusion susceptibility testing of cefotaxiime have been recently proposed (1) and include the use of 5-or 30-,ug disks, depending on the organism being tested.…”
mentioning
confidence: 99%